An array of nuclear microtubules reorganizes the budding yeast nucleus during quiescence - Laporte, Damien (The Rockefeller University Press, 2013)
The microtubule cytoskeleton is a highly dynamic network. In dividing cells, its complex architecture not only influences cell shape and movement but is also crucial for chromosome segregation. Curiously, nothing is known about the behavior of this cellular machinery in quiescent cells. Here we show that, upon quiescence entry, the Saccharomyces cerevisiae microtubule cytoskeleton is drastically remodeled. Indeed, while cytoplasmic microtubules vanish, the spindle pole body (SPB) assembles a long and stable monopolar array of nuclear microtubules that spans the entire nucleus. Consequently, the nucleolus is displaced. Kinetochores remain attached to microtubule tips but lose SPB clustering and distribute along the microtubule array, leading to a large reorganization of the nucleus. When cells exit quiescence, the nuclear microtubule array slowly depolymerizes and, by pulling attached centromeres back to the SPB, allows the recovery of a typical Rabl-like configuration. Finally, mutants that do not assemble a nuclear array of microtubules are impaired for both quiescence survival and exit.